2018
DOI: 10.1242/dmm.033100
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis in context: modeling the tumor microenvironment with cancer-on-a-chip approaches

Abstract: Most cancer deaths are not caused by the primary tumor, but by secondary tumors formed through metastasis, a complex and poorly understood process. Cues from the tumor microenvironment, such as the biochemical composition, cellular population, extracellular matrix, and tissue (fluid) mechanics, have been indicated to play a pivotal role in the onset of metastasis. Dissecting the role of these cues from the tumor microenvironment in a controlled manner is challenging, but essential to understanding metastasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 122 publications
0
75
0
Order By: Relevance
“…In order to develop a reliable tool for personalized cancer therapy and drug development, it is essential to preserve the key characteristics of the original tumor. Recent advances on three dimensional (3D) platforms through the use of labon-chip and microfluidic devices [17] have provided an enormous opportunity to better stimulate the function and biology of TME and to bridge the translational gap between preclinical and clinical settings [18].…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop a reliable tool for personalized cancer therapy and drug development, it is essential to preserve the key characteristics of the original tumor. Recent advances on three dimensional (3D) platforms through the use of labon-chip and microfluidic devices [17] have provided an enormous opportunity to better stimulate the function and biology of TME and to bridge the translational gap between preclinical and clinical settings [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells were implanted to construct a murine model that showed that the higher levels of P2X7R caused changes in the tumour stroma via TAM recruitment and angiogenesis, as well as increased CSC features. The tumour microenvironment is critical in the process of metastasis 41 . As previously study, metastasis involves M2 but not M1 macrophages that support tumour formation 42 .…”
Section: Discussionmentioning
confidence: 79%
“…Most current reviews either focus on specific fields such as cell migration and 3D cell culture or highlight the biological applications of in vitro tumor models [14][15][16], with limited emphasis on their contribution to anti-cancer drug screening and development. This review aims to provide readers with a detailed discussion on the current state-of-art microfluidics-based tumor models, with a special focus on their application in anti-cancer drug screening and the engineering approaches to recapitulate the tumor microenvironment ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%